Designing an Online To-Do-List System to Support Student Productivity in Managing Lecture Assignments and Islamic Boarding School Activities - Made Asri Syaiba Almihda Hasan; Faradiba Isqi Al-Azizih; Ahmad Hamdani (Yayasan Kita Menulis, 2026)
This study on designing an online To-Do-List system intended to assist mahasiswa santri (Islamic boarding school students attending university) in increasing productivity in managing academic tasks and pesantren actvities. Mahasiswa santri pften struggle to balance academic responbilities with demanding religious routines. To address this issue, the system is developed in the from of a web-based application that can be accessed flexibly. The main features provided include task recording, schedule reminders, and activity progress monitoring. The system design is developed using the prototype method, allowing users to provide direct feedback throughout the design process. The resulting interface and system flow align with user needs and show that the proposed system has the potencial to help users manage their time more efficiently and foster discipline toward their daily schedules. Thus, this system can serve as a digital solution that supports the balance between academic and religious activities for mahasiswa santri. Keyword : To-Do-List System, Productivity, Mahasiswa Santri, Web-Based Application, Prototype Method